Highly Efficient Multi‐Tasking Porphyrin‐Based Chemosensor for Mercury Ions. Issue 11 (17th March 2022) - Singha, Jyotirlata; Patra, Diptendu; Kumar, Pawan; Shunmugam, Raja
Abstract: Porphyrin‐based monomeric and polymeric sensors are emerging as a desirable alternative to efficient sensors due to their unique optical properties and biocompatibility. An efficient new sensor Acpmono and Acppoly were designed and synthesized for selective and efficient mercury detection at ppm‐level. UV‐visible and fluorescence spectroscopic techniques were studied for the sensing performance of both the monomeric and the polymeric sensors. Mechanism of interaction between sensors was confirmed by proton nuclear magnetic resonance (NMR) titration, Ultraviolet‐visible and fluorescence spectroscopic titration, mass spectrometry, time‐correlated single‐photon count (TCSPC) study. Furthermore, a "turn‐off" mode has been established to detect noble heavy metal mercury (Hg 2+ ) by quenching the red fluorescence of sensor molecules. The real‐time application of Acpmono and Acppoly were studied by preparing paper strips and detecting Hg 2+ from beauty products in a facile way. Cell viability was evaluated for sensors Acpmono and Acppoly to living HeLa cells using the MTT assay technique to investigate the applicability of the sensors in a biological medium. Based on the MTT assay data of both monomeric and polymeric sensors, the cell imaging of endogenous Hg 2+ ions was explored in living HeLa cells. Abstract : We have designed porphyrin‐based monomeric (Acpmono) and polymeric (Acppoly) sensors for selectively and efficient detection of Hg (II) at the PPM level (LOD=20 nM and 6.3 nM) in an aqueous environment. The simultaneous 'turn‐on' was observed from pink to green (colorimetrically) and 'turn‐off' by quenching red fluorescence (fluorometrically). Furthermore, for real‐time application, MTT assay was done for sensors to living HeLa cells, and the cell imaging of endogenous Hg 2+ ions was explored in living HeLa cells.